Gsol ʼdebs leʼu bdun paʼi lo rgyus dmigs rim phan yon daṅ bcas pa bźugs so - Karma-chags-med, Gnas-mdo, 1610-1678 (s.n., 1972)
Exegesis of the Gsol ʼdebs leʼu bdun ma, 14th century Nyingmapa Lamaist devotional work extolling Padmasambhava "rediscovered" by Gter-ston Bzaṅ-po-grags-pa.